CARDHOLDERS’ ATTITUDE AND BANK CREDIT CARD USAGE IN MALAYSIA: AN EXPLORATORY STUDY - T. Ramayah; Nasser Noor; Aizzat Mohd. Nasurdin; Lim Hee Choo (Asian Academy of Management Journal, 2002)
The study is aimed at validating attributes that influence the differences in attitudes among active and inactive cardholders. By focusing on relevant attributes that have been identified, it is believed that credit card issuing banks can position themselves effectively via their marketing strategies to activate their existing cardholders' usage rate as well as to attract new active cardholders. Thirteen important attributes were used to measure credit cardholders' attitude. These attributes include acceptance level, credit limit, interest-free repayment period, annual fee, application approval period, ancillary functions, handling of cardholders' complaints, issuing bank image, gift/bonus to new applicants, card design, leaflet to describe the card,and advertising by the issuing bank. Acceptance level, credit limit, interest free repayment period, ancillary functions, handling of cardholders' complaints, bank image, and bank advertising were found to be the most important attributes that influenced cardholders' attitudes in distinguishing active from inactive cardholders. Based on the results of the study, several suggestions are forwarded to credit card issuing banks as a step to stimulate credit cardholders' usage level. Among these are to work closer with various retailers to promote the credit card payment mode, to provide adequate credit limit to cardholders, to extend interest free repayment period from 20 days to 30 days, to implement strategic alliances with firms involved in travelling, entertainment, insurance, and telecommunications and, to advertise more so as to create a brand name for the issuing bank.